Retrospective study of patients with herpes simplex encephalitis and positive CSF PCR. - Polchai Pleumpanupat (2018)
OBJECTIVE: To determine the clinical presentations, laboratory and imaging findings of patients with HSE and positive CSF PCR then compare these with information from other viral encephalitis patients in order to find clinical clues that might help clinicians in early diagnosis and treatment of HSE while awaiting for the CSF PCR result. MATERIAL AND METHOD: A patient group with both HSE and positive CSF PCR and a control group of patients with other viral encephalitis were identified from Siriraj Hospital database within the period of 1997-2006. Medical notes of these patients were reviewed and relevant information, including clinical, laboratory and imaging study, were extracted. Then, descriptive statistics, unpaired t-test and Fisher's exact test were performed with the purpose to determine any clinical or laboratory clues that are significantly different between these two groups, which might help clinicians in making an early diagnosis of HSE. RESULTS: Seven HSE cases and 22 cases in control group were included. Fever, headache, alteration of consciousness, behavioral change, neck stiffness are the most commonly found clinical presentations in HSE patients with CSF PCR positive. CSF examination show CSF leukocytosis with lymphocyte predominate, decreased CSF:blood glucose ratio and elevated CSF protein in all cases. However, no single clinical or laboratory finding helps in differentiating HSE with positive CSF PCR from other viral encephalitides, except radiological abnormalities of temporal lobe, which yields a positive predictive value of 0.5 and a negative predictive value of 0.93. CONCLUSION: Our study showed that HSE shares common clinical and laboratory findings with other viral encephalitides, except for temporal lobe involvement. Early diagnosis is important and empirical acyclovir should be commenced early in patients with viral encephalitis, especially for those with radiological abnormalities on the temporal lobe.